Empirical Studies of Momentum Strategies in Hong Kong and Japan Stock Markets - Zhu, Qianlan (2011)
This paper empirically investigate the profitability of 6-6 month momentum strategy (Jegadeesh and Titman, 1993) in Hong Kong and Japan stock markets. The abnormal returns are found only in Hong Kong market, and the short position of “losers” in both markets did not generate profits for momentum strategy. As examining the sources of profits, both cross sectional and time varying variations contribute to the profits.